2020
DOI: 10.1101/2020.05.12.091900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Naturally acquired blocking human monoclonal antibodies toPlasmodium vivaxreticulocyte binding protein 2b

Abstract: Plasmodium vivax preferentially invades reticulocytes and recognition of these cells is mediated by P. vivax Reticulocyte Binding Protein 2b (PvRBP2b) binding to human Transferrin receptor 1 (TfR1) and Transferrin (Tf). Longitudinal cohort studies in Papua New Guinea, Thailand and Brazil show that PvRBP2b antibodies are correlated with protection against P. vivax infection and disease. Here, we isolated and characterized anti-PvRBP2b human monoclonal antibodies from two individuals in Cambodia with natural P. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Isolation and characterization of anti-PvRBP2b human monoclonal antibodies (mAbs) in Cambodian patients proved the inhibitory role of naturally acquired antibodies against P . vivax invasion [ 19 ]. The majority of PvRBP2b human mAbs were connected to epitopes within amino acids 169–470, and 470–652, and only two mAbs were related to 969–1454 residues [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Isolation and characterization of anti-PvRBP2b human monoclonal antibodies (mAbs) in Cambodian patients proved the inhibitory role of naturally acquired antibodies against P . vivax invasion [ 19 ]. The majority of PvRBP2b human mAbs were connected to epitopes within amino acids 169–470, and 470–652, and only two mAbs were related to 969–1454 residues [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…vivax invasion [ 19 ]. The majority of PvRBP2b human mAbs were connected to epitopes within amino acids 169–470, and 470–652, and only two mAbs were related to 969–1454 residues [ 19 ]. To know whether antigenic diversity and amino acid replacements can impact on the recognition of epitopes by antibodies, epitope prediction was performed and the results showed that of 44 substitutions, 14 replacements were located in the linear and conformational B-cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations